Nutrient and Heavy Metal Content of Three Leafy Vegetables (Talinum fructicosum (L.) Juss., Vernonia amygdalina Delile, Solanum macrocarpon L.) from an Effluent-Receiving Wetland in the Douala Bassa Industrial Development Zone, Cameroon: Implications for - Charleine, Djouego Sob; Neculina, Anyinkeng; Egbe, Awo Miranda; Tabot, Pascal Tabi; Bernard, Tiencheu; Ambo, Fonge Beatrice (Asian Pacific Journal of Environment and Cancer, 2024)
Objective: Contamination by heavy metals in soil, water, and agricultural products is a significant concern, particularly affecting wetland ecosystems. This investigation aimed to assess the levels of heavy metals (Pb, Cd, Hg, Cu, As, Zn, and Ni) and nutritional values in three highly cultivated leafy vegetables (Talinum fructicosum (L.) Juss., Vernonia amygdalina Delile, Solanum macrocarpon L.) collected from a polluted coastal wetland. Additionally, we evaluated the potential health hazards for both adults and children.” Methods: The mature and young leaves with succulent stems were collected during the dry and rainy seasons, transported to the laboratory, processed and then analysed for nutritional contents according to standard methods, and heavy metals was measured with atomic Absorption Spectrophotometer. Results: The three leafy vegetables were found to be low in fat (0.85±2.19%), protein (3.01±9.06%), ash (0.68±5.03%), and carbohydrates (1.34±4.54%). During both seasons, the Cd (0.45±2.49%), Cu (208.34-927.41%), and Zn (29.39±3554.5%) content in leafy vegetables was extremely high, surpassing the WHO/FAO safe limits. The Hazard Index (HI) values were all greater than (>) one (1) for both adults (32.259±67.31) and children (67.310±489.89). Total carcinogenic health risk (TCR) values for Pb, Cd, and AS due to consumption of the three vegetables for adult (0.008±0.052) and children (0.018±0.109) also exceeded the maximum threshold value of 10−4. From our findings, inhabitants who consume these contaminated vegetables are exposed chronically to metal pollution with carcinogenic and non-carcinogenic risks. Conclusion: In the light of these finding, policies and regulations should be reinforced regarding the discharge of untreated effluents into the environment and the prohibition of the growing of leafy vegetables should be strengthened.